The Influence Of Working Capital Turnover, Company Size And Debt To Equity Ratio On The Profitability Of Food And Beverage Subsector Companies Listed On Th - Khairunnisa, Khairunnisa; Nurismalatri, Nurismalatri (Doktoral Ilmu Manajemen, Universitas Pasundan, 2025)
This study aims to analyze the effect of Working Capital Turnover, Firm Size, and Debt to Equity Ratio on Profitability in eight food and beverage sub-sector companies during the 2019-2023 period. Using a quantitative method with panel data regression and analysis conducted through Eviews12, this research applies Descriptive Statistical Analysis, Classical Assumption Tests, as well as T-Test and F-Test. The results indicate that, partially, Working Capital Turnover, Firm Size, and Debt to Equity Ratio do not have a significant effect on Profitability. However, simultaneously, these three variables influence Profitability, as shown by F-statistic 15.97120 > F-table 2.866. The coefficient of determination reveals that the research variables explain 84.63% of Profitability, while the remaining 15.37% is influenced by other factors not discussed in this study.